Comparing the Environmental Impacts of Alkali Activated Mortar and Traditional Portland Cement Mortar using Life Cycle Assessment. Issue 1 (October 2015) - Matheu, P S; Ellis, K; Varela, B
Abstract: Since the year 1908 there has been research into the use alkali activated materials (AAM) in order to develop cementitious materials with similar properties to Ordinary Portland Cement. AAMs are considered green materials since their production and synthesis is not energy intensive. Even though AAMs have a high compressive strength, the average cost of production among other issues limits its feasibility. Previous research by the authors yielded a low cost AAM that uses mine tailings, wollastonite and ground granulated blast furnace slag (GGBFS). This mortar has an average compressive strength of 50MPa after 28 days of curing. In this paper the software SimaPro was used to create a product base cradle to gate Life Cycle Assessment (LCA). This compared the environmental impact of the AAM mortar to an Ordinary Portland Cement mortar (PCHM) with similar compressive strength. The main motivation for this research is the environmental impact of producing Ordinary Portland Cement as compared to alkali activated slag materials. The results of this LCA show that the Alkali Activated Material has a lower environmental impact than traditional Portland cement hydraulic mortar, in 10 out of 12 categories including Global Warming Potential, Ecotoxicity, and Smog. Areas of improvement and possible future work were also discovered with this analysis.